2.7(14q+7.2)-3q=9

Simple and best practice solution for 2.7(14q+7.2)-3q=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2.7(14q+7.2)-3q=9 equation:


Simplifying
2.7(14q + 7.2) + -3q = 9

Reorder the terms:
2.7(7.2 + 14q) + -3q = 9
(7.2 * 2.7 + 14q * 2.7) + -3q = 9
(19.44 + 37.8q) + -3q = 9

Combine like terms: 37.8q + -3q = 34.8q
19.44 + 34.8q = 9

Solving
19.44 + 34.8q = 9

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-19.44' to each side of the equation.
19.44 + -19.44 + 34.8q = 9 + -19.44

Combine like terms: 19.44 + -19.44 = 0.00
0.00 + 34.8q = 9 + -19.44
34.8q = 9 + -19.44

Combine like terms: 9 + -19.44 = -10.44
34.8q = -10.44

Divide each side by '34.8'.
q = -0.3

Simplifying
q = -0.3

See similar equations:

| 4(t-3)+8t=6(2t+2)-9 | | 5p=65 | | (X+20)=x | | 14r^3-23r^2+8r=0 | | 30-10n=20 | | -20+10n=40 | | 4e^2x-3=2 | | -10-2n=20 | | 2t+11t=114 | | 4+12p-2=8p+74-4p | | 2+3p=12+2p | | y=2y-2 | | .9w-.6w+.2w=2 | | 8x-9+3x=24 | | 16+2x=50 | | -5x+6=2(x-5)+1 | | 3(2x+10)=108 | | 6x+2(7-x)+10=20 | | (4y+6)-(8+y)=3y-(4y+6) | | 19x+124=48 | | n+14=12-3n | | 4(3.14)5= | | x-97=-12 | | 4+5v=-21 | | 2(x+20)-15=51 | | 8p+9=14+7p | | 6x-2x+8=20 | | 26.50+0.15x=14.50+0.25 | | 5c-20= | | 1.4=3.8+1w | | |h+4|=11 | | 2(x+6)+2(x-5)=54 |

Equations solver categories